Effect of Phacotrabeculectomy on Ocular Biometric, Gonioscopic and Intraocular Pressure In Patients With Primary Angle Closure Glaucoma - Riskha Pangestika; Fifin L. Rahmi; Maharani Maharani (Majalah Oftalmologi Indonesia, 2022)
Objectives: The objective of this study is to have an expanded evaluation on the effect of phacotrabeculectomy on ocular biometric (ACD/anterior chamber depth, lens thickness), gonioscopic and intraocular pressure (IOP) in primary angle closure glaucoma (PACG). Methods: A cohort study of PACG patient who underwent phacotrabeculectomy from September 2018- March 2019 at Dr.Kariadi hospital. Preoperative secondary data of baseline IOP, ACD, lens thickness, and gonioscopy were obtained from medical record. Postoperative primary data of IOP, ACD, and gonioscopy were obtained 2 weeks after surgery. Results: Thirty eyes from 23 patients had preoperative and postoperative mean IOP (26,20±2,24 and 18,35±2,49), mean ACD (2,46±0,37 and 3,40±0,40), mean gonioscopic score (4,97±0,96 and 8,33±1,63), mean preoperative lens thickness (4,58±0,39). There were significant differences between IOP, ACD and gonioscopic score (<0,001) before and after phacotrabeculectomy. The greater lens thickness was associated with IOP reduction ( <0,001 r=0,756), increased ACD ( 0,005 r=0,498), and increased gonioscopic score ( <0,001, r=0,802). The positive correlation can be seen between gonioscopic score and ACD ( <0,001 r=0,666) and the negative correlation between IOP and ACD ( <0,001 r=0.683), IOP and gonioscopic score ( <0,001 r=0,876). Conclusion: Phacotrabeculectomy may be effective in reducing IOP, increasing ACD, and gonioscopic scores significantly in PACG patients. Lens thickness may be positively